Pemanfaatan Pupuk Organik Cair Urine Sapi Berbagai Konsentrasi Terhadap Pertumbuhan dan Hasil Bayam Hijau (Amaranthus hybridus L.) - Sugiarto; Putri, Alifiyah Firanda; Sholihah, Anis (Universitas Islam Malang, 2023)
The demand for green spinach in Indonesia is increasing every year in line with the increase in population, but the production of green spinach in Indonesia is still insufficient to meet domestic needs which causes the large import value of green spinach to occur. The main requirement in increasing plant productivity during the growth period is the availability of nutrients for plants. In the soil there are nutrients available for plants naturally. However, not all soils can provide sufficient nutrients for plants. Thus, fertilization is needed. In an effort to increase land productivity in a sustainable manner, it can be done by utilizing agricultural or livestock wastes that are around. This study aims to determine the effect of giving cow urine liquid organic fertilizer with various appropriate and optimum concentrations on the growth and yield of green spinach (Amaranthus hybridus L.). This research was conducted using a simple randomized block design (RBD) consisting of 5 treatments with cow urine POC concentration U0 = 0 ml/L U1 = 50 ml/L U2 = 100 ml/L U3 = 150 ml/L U4 = 200 ml/ L. The variables observed were growth variables (plant height and number of leaves) and yield variables (harvest index, total fresh weight, economic fresh weight, total dry weight and economic dry weight). The data obtained in the analysis of variance (ANOVA) at the level of 5%. If there is a real effect, do a 5% BNT test. Regression analysis was also carried out to determine the proper and optimum POC concentration of cow urine. Keywords: Liquid Organic Fertilizer, Concentration, Amaranthus hybridus L.